Collateral damage: has the COVID-19 pandemic more strongly impacted medical research than other scientific areas? - Farji Brener, Alejandro Gustavo (2023)
The principle of resource allocation states that diversion of resources to attend a function may compromise others. The COVID-19 pandemic required a rapid response with a justifiable relocation of equipment, funds and human resources. Based on the ecological principle of allocation, we tested whether the relocation of resources to support COVID-19 research was more detrimental to medical research than to research in other scientific areas. We compared the yearly number of published articles from 2015 to 2021 using disease-related keywords and non-medical scientific keywords. Contrary to the expectation, we found an abrupt reduction in the publication rates in all research areas from 2019 to 2020 or 2021, compared to the pre-pandemic period (2015–2019). The allocation effect on medical research may be overshadowed by stronger effects of the pandemic, or it may become evident in the coming years. The drastic reduction in published papers could have negative consequences for scientific advancements, including understanding and curing diseases other than COVID-19 that strongly affect humanity.